Nicolas Castel, Poursuite du salaire ou revenu différé ? La réforme des retraites en France (1987-2005) - Nicolas Castel (Revue de la Régulation)
This dissertation in sociology analyses the changes that took place in the French retirement system from the end of the 1980’s to the beginning of the 21st century, and the discourse of trade unions and experts involved in bringing about these changes. The national pay-as-you-go retirement system was transformed under the influence of the concept of “national solidarity,” of pressures to strengthen the link between benefits and contributions, and of calls for funding pensions. Throughout this process, the impact of the retirement system on the status of wage earners never emerged as an issue. This theme was totally absent from the discourse of experts and of those in power, and it was rarely touched on by trade unions. This dissertation considers retirement pensions to be a component of wages and analyses the impact of changes in social protection on wages. These changes have been wide sweeping: they affect the very definition of what it means to be a retiree and of the retiree’s relationship to time and, more broadly, the definition of the kinds of work to which monetary value can be ascribed. This dissertation argues that the concept of wages cannot be reduced to an economic object, and that it should be considered a “total social fact,” as defined by Marcel Mauss.